Structural, morphological and optical investigation of beta-Ag2MoO4 microcrystals obtained with different polar solvents - Cunha, F. S.; Sczancoski, J. C. [UNESP]; Nogueira, I. C.; Oliveira, V. G. de; Lustosa, S. M. C.; Longo, E. [UNESP]; Cavalcante, L. S. (Royal Soc Chemistry, 2015)
This communication reports the formation of beta-silver molybdate (beta-Ag2MoO4) microcrystals synthesized by a simple precipitation method using different polar solvents (water, methanol, ethanol, 1-propanol and 1-butanol). These crystals were structurally characterized by means of X-ray diffraction (XRD) and Rietveld refinement. The crystal shapes and sizes were observed by field emission scanning electron microscopy (FE-SEM). Their optical properties were analyzed by ultraviolet-visible (UV-vis) diffuse reflectance spectroscopy. XRD patterns and Rietveld refinement data indicated all crystals have a spinel-type cubic structure. FE-SEM images revealed the crystals tend to increase the average size with reduction in the degree of polarity of the solvent. Finally, beta-Ag2MoO4 microcrystals exhibited a dependence of optical band gap energies (from 3.22 to 3.38 eV) on the intermediary energy levels.